Cuidado, diversidade e acessibilidade: desafios contemporâneos para a educação pública - Hermann Sousa Silva; Claudia Thaysa Reis de Moura Santos; Elenilda Rodrigues dos Santos; Alanna Klyvia Mourão Brito; Mariângela Knitter Barros; Maria Célia Soares de Farias; Maria Telma Barbosa Gomes; Rosana Maria de Moraes Rodas; Maria dos Prazeres Santos Medeiros; Adriane Teixeira Baracho; Hyngrid Assíria Amorim Costa; Luciana Lima dos Santos; et al. (Revista ft, 2026)
This study analyzes contemporary challenges in Brazilian public education through the articulation of care, diversity and accessibility, understood as inseparable dimensions of the right to education and health promotion. A qualitative bibliographic review was conducted, with a thematic synthesis of 17 Portuguese-language articles published between 2022 and 2025, retrieved from open-access scientific journals and selected for thematic relevance. The analysis was organized into three axes: care and health in educational settings; diversity, discrimination and equity; accessibility, ableism and student retention. The findings show that expanded access to public education does not eliminate attitudinal, pedagogical, communicational, architectural and institutional barriers, nor the effects of racism, sexism, ableism and other forms of discrimination on educational experiences. Psychological distress and retention difficulties also require intersectoral responses, student participation, continuing education and organized support networks. It is concluded that genuinely inclusive public education depends on rights-based management, non-medicalizing care, universal accessibility and recognition of diversity as a principle of social justice.